Pengukuran Titik Beku Larutan Asam Asetat-Asetamida - Perpustakaan UGM, i-lib ([Yogyakarta] : Jur. Budidaya Pertanian Fak. Pertanian UGM, 1996)
In this study, the freezing point of the acetic acid-acetamide system has been determined using a modified Beckmann freezing point apparatus throughout the entire range of concentration. The data obtained are compared to the data of the previous investigators. The results of the present work agree exellently with the data of the two other investigators for the acetamide concentration from 0 17701 % up to 30 mol % (Kremann et al., 1922